1996
DOI: 10.1111/j.1744-7348.1996.tb07321.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies for the detection and differentiation of faba bean necrotic yellows virus isolates

Abstract: Murine monoclonal antibodies (MAbs) were produced for the detection of faba bean necrotic yellows virus (FBNYV), an isometric ssDNA virus belonging to a new, yet unnamed genus of plant viruses. A total of 19 FBNYV-specific MAbs were obtained from three fusion experiments and characterised by determining their immunoglobulin types and titres as well as their corresponding epitopes. At least six distinct epitopes were revealed on FBNYV particles of different virus isolates. Only two MAbs reacted with SDS-dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
2
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 31 publications
0
54
2
1
Order By: Relevance
“…Moreover, FBNSV-[ET:Hol:97] failed to react with the FBNYV MAbs 1-3D8, 2-5H9, and 3-4A5. For instance, MAbs 2-5H9 and 3-4A5 reacted in TAS-ELISA with FBNYV but not with MDV and a nanovirus in faba bean samples originating from Ambo, Ethiopia (18). This suggested that FBNSV-[ET:Hol:97] is serologically distinct from Syrian and Egyptian isolates of FBNYV as well as from MDV.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, FBNSV-[ET:Hol:97] failed to react with the FBNYV MAbs 1-3D8, 2-5H9, and 3-4A5. For instance, MAbs 2-5H9 and 3-4A5 reacted in TAS-ELISA with FBNYV but not with MDV and a nanovirus in faba bean samples originating from Ambo, Ethiopia (18). This suggested that FBNSV-[ET:Hol:97] is serologically distinct from Syrian and Egyptian isolates of FBNYV as well as from MDV.…”
Section: Resultsmentioning
confidence: 91%
“…Each of two female BALB/c mice (2 to 3 months old) received a subcutaneous injection of ϳ75 g of FBNSV virions in 150 l containing 50% Freund's incomplete adjuvant. Booster injections, fusion experiments, selection of hybridomas, and cloning were essentially conducted as described previously (1,18). For hybridoma selection by TAS-ELISA, however, FBNYV IgG was used for the trapping of antigen from extracts of FBNYV-and FBNSV-infected faba bean plants as well as from noninoculated plants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A serological study with a range of monoclonal antibodies to FBNYV showed that an MDV isolate from Japan shared four of the six identified FBNYV epitopes with typical FBNYV isolates from Syria and Egypt, suggesting that FBNYV and MDV might be strains of the same virus (Franz et al, 1996). Although FBNYV and MDV are most similar in one of their non-Rep proteins (90n8 % identity) and have two apparently closely related Rep proteins (88n3 and 89n8 % identical), their coat protein amino acid sequences were 83n6 % identical (Sano et al, 1998), and they differed in their four other non-Rep proteins by 23 %.…”
Section: Discussionmentioning
confidence: 99%
“…It is the causal agent of a destructive disease of chickpea in some arid regions, including countries in north Africa, west Asia and southern Europe (Katul et al 1993;Franz et al 1996). FBNYV is known to infect more than 50 legume species.…”
Section: Breeding For Resistance To Virusesmentioning
confidence: 99%